Phase change material/heat pipe and Copper foam-based heat sinks for thermal management of electronic systems - Hayat, M.A. (Elsevier Ltd, 2020)
Phase change material (PCM) has been extensively used for their thermal management but due to low conductivity that hinders the performance of a system. Since heat pipe and porous materials both have high thermal conductivities, they can be used to form hybrid system with PCM which significantly enhance the heat transfer capability of PCM. In current research of heat pipe, copper foam (pore density 40PPI and porosity 93) and PCM based heat sinks are used to inspect the thermal performance of heat sink with respect to time by varying heat fluxes. ââRT-35HCâ PCM, copper foam and gravity assisted heat pipe with and without cooling fan are used in experimental investigation. The results showed after 6000 s when charging ends hybrid cooling (Foam-PCM-HP) with fan have maximum temperature reduction i.e. 47, 51 and 54 at heat flux of 2, 2.5 and 3 kW/m2 respectively. Similarly, for discharging hybrid cooling with fan showed excellent cooling results at all heat fluxes. Â© 2020 Elsevier Ltd